Hábitos ecológicos y conciencia ambiental en docentes de la Institución Educativa Inicial N° 1016 Urarinas, Loreto 2022 - Quevedo Huani, Mariciela Estela (2023)
The present study responds to the non-experimental design of a descriptive correlational research type with a quantitative approach. An estimated population of 26 teachers was used as an example, where a non-probabilistic sample was used. The technique used was the interview, using the questionnaire as a test instrument. Three specialists in the field endorsed them and the Crombach's alpha statistic was used to determine their reliability. This indicates that the results are reliable. The tables of percentages and data averages were examined using statistical graphs .The Shapiro-Wilks test of normality of fit was similarly performed, for sample ≤ 50.Using Pearson's parametric correlation statistical method , it was possible to compare the hypotheses .The following conclusion was the most pertinent: According to the general hypothesis of the research , the relationship between environmental awareness and ecological habits among teachers of IE N° 1016 “Urarinas” was direct, positive and statistically significant (sig.=,000; p.005).